The Myth of Academics' Non-interference in Legislatures. (May 2022) - Zelizer, Adam
This essay discusses the history and ethics of academics' intervention in the legislative process. Academics, and even our professional associations, have explicitly worked to change legislative operations through advocacy and consulting. I argue that subjecting such interventions to the research process to evaluate their effects makes them more ethical and transparent. Research is monitored and guided by professional associations, institutional review boards, and journals in ways that advocacy and consulting are not. If academics are already intervening in legislative processes, such efforts will be more fruitful if conducted as part of a research program. This program, which I call "evidence-based legislating, " aims to improve the evaluation of legislative processes just as the movement for evidence-based policymaking reshaped academics' and lawmakers' approach to policy evaluation.